Study On Role Of Excitatory Amino Acid Input On Rostral Ventrolateral Medulla Neurons And Assessment Of Peripheral Vascular Reactivity In Obesity-Induced Hypertension - Suhaimi, Farah Wahida (2010)
Rostral ventrolateral medulla (RVLM) plays a pivotal role in the tonic and phasic regulation of blood pressure. The present study was carried out to determine whether the excitatory amino acid (EAA) input to the RVLM contributed to elevated blood pressure and to assess the peripheral vascular reactivity in obesity-induced hypertension. Male Sprague-Dawley rats were fed with low-fat diet or moderately high-fat (MHF) diet for 16 weeks. Then, rats on MHF diet were segregated into obesity-prone (OP) and obesity-resistant (OR) rats based on the body weight distribution. OR rats were defined as rats with body weight similar or less than control rats (LF rats) while OP rats were defined as rats with greatest body weight. At week 16, rats were subjected to study the role of EAA on RVLM neurons or to study the peripheral vascular reactivity in obesity-induced hypertension. In the former study, L-glutamate (1 nmol) and kynurenic acid (KYN) at concentrations of 4 nM, 40 nM and 4 μM were microinjected into RVLM and hexamethonium (20 mg/kg) was administered intravenously. Brain stem was removed for histological verification and adiposity index was calculated. OP rats exhibited significantly larger weight gain, higher adiposity index and also elevated blood pressure.